The Application of Interactivity in Modern Food Packaging Design - Sun, Xiaohua (Transactions on Social Science, Education and Humanities Research, 2023)
With the development of economy and the improvement of people's aesthetic level, the packaging design of food is becoming more and more novel and exquisite in the market competition, which is liked by different consumer groups. This paper first discusses the concept of interactivity, then analyzes the significance of interactivity in food packaging, focusing on the creative forms of interactivity in food packaging, hoping to enhance the interaction, interest and richness of products through a variety of modeling techniques, and ultimately enhance the influence and sales volume of products.